Educar e civilizar o Brasil na obra do médico missionário João Gomes da Rocha : intelectual da educação protestante (1924-1957) - Freitas Junior, Cleofas Lima Alves de (2023)
The thesis consisted of analyzing the performance of the missionary doctor João Gomes da Rocha as an intellectual of Protestant education who, in his work, thought about the construction of a modern, civilized and educated Brazil, in the period from 1924 to 1957. Thus, three assumptions stand out during the research: a) The various aspects of Rocha's constitution as an intellectual of Protestant education in Brazil, with emphasis on the educational, religious and musical heritage bequeathed by the Kalley couple and his work as a missionary doctor; b) his active participation in thinking about the transformation of Brazil through education through music in his musical work; c) his active role in thinking about Brazil through education through history in his historiographical work. Based on the framework of Linguistic Contextualism, studies of cultural history, women's history and gender relations, using notions such as representations, sensitivity, identity and appropriation. The results were organized into three sets during the research. In the first set, the constitution of João Gomes da Rocha as an intellectual of Protestant education in Brazil in the first decade of the 20th century was analyzed, through a close look at the fragments that formed his life and intellectual project, especially his writing itself, when Rocha's objective, syntactic and reductionist official narrative about his life was surpassed. Based on Sirinelli, it was demonstrated that Rocha was an intellectual of Protestant education in Brazil, a “cultural creator” who participated in artistic and literary production, through an active role in the construction of knowledge in our country from the Protestant perspective. He was also a “cultural mediator” who contributed to disseminating and popularizing the knowledge of this creation from the perspective of the Protestant faith, because he engaged and intervened in actions that legitimized his defense of the modernization of Brazil with the implementation of Protestantism. In the second, there were representations of Civilized Protestant Brazil in the Psalms and Hymns Collection, compiled by João Gomes da Rocha, published in 1924, which sought to promote Protestant education through music among the faithful. This instruction was achieved through a thorough reading of the various images produced in the songs dedicated to the education of children, worship in homes, daily schools, Sunday schools, young people and the country. This feat was divided into three parts: the first deals with children's education; the second refers to family education and the third to education in schools to form a civilized nation. The objective of the Collection was demonstrated to be a “useful” and “attractive” book for the faithful to worship and praise God with quality music. As well as the importance of music for the implantation of Protestant civilization in the world, which consisted of promoting salvation through evangelization: publishing the unique love for humanity in Jesus Christ and faithfully fulfilling the noble and sublime evangelizing enterprise entrusted by Himself to your Church. In the third set, the representations of Protestant Education in Brazil in the 19th Century were analyzed, formulated by Rocha, in the Memories of the Past Collection, in promoting education through history. In this Collection, in four volumes, he educated the Protestant faithful in the first half of the 20th century, with a historical narrative of the civilizational program undertaken by the couple Robert Reid Kalley and Sarah Poulton Kalley, resulting in the founding of the Fluminense Evangelical Church at the end of the 19th century. In this way, Rocha, in his Collection, created different images about being Protestant, with the Kalley couple as protagonists and the active participation of the faithful of the Fluminense Evangelical Church. In this way, it was possible to classify these images of Protestant education into three parts: a) biblical societies, Brazilian reality and religious intolerance; b) books, reading, the centrality of the Bible and schools; d) marriage and family education.